2018
DOI: 10.31491/csrc.2018.9.020
|View full text |Cite
|
Sign up to set email alerts
|

MiR-449b inhibits the migration and invasion of colorectal cancer cells through the negative regulation of MMP2

Abstract: Background: An increasing number of miRNAs were confirmed to be involved in the initiation and progression of colorectal cancer (CRC) by acting as cancer suppressor genes and oncogenes. The purpose of this study was to uncover the role of miR-449b in CRC and its underlying mechanisms. Methods: The expression profile of miR-449b in human CRC tissues and cell lines was determined using quantitative real-time polymerase chain reaction (qRT-PCR) analysis. The effect of miR-449b on CRC was assessed by CRC cell migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The genetic materials encapsulated by MVs, such as microRNAs (miRNAs), can be transferred from tumor cells to adjacent cells, such as endothelial cells, thus affecting the tumor microenvironment. 17,18 For instance, miR-1246 encapsulated by colorectal cancer cellderived MVs can activate PML-induced Smad 1/5/8 signaling in endothelial cells, thereby promoting the proliferation, migration and angiogenesis of endothelial cells. 19 According to miRNA expression analysis in umbilical cord blood MVs using miRNA PCR arrays, miR-377 was detected in MVs from umbilical cord blood, 20 indicating that miR-377 can be carried by MVs.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic materials encapsulated by MVs, such as microRNAs (miRNAs), can be transferred from tumor cells to adjacent cells, such as endothelial cells, thus affecting the tumor microenvironment. 17,18 For instance, miR-1246 encapsulated by colorectal cancer cellderived MVs can activate PML-induced Smad 1/5/8 signaling in endothelial cells, thereby promoting the proliferation, migration and angiogenesis of endothelial cells. 19 According to miRNA expression analysis in umbilical cord blood MVs using miRNA PCR arrays, miR-377 was detected in MVs from umbilical cord blood, 20 indicating that miR-377 can be carried by MVs.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the diagnostic effects of the serum tumor markers on the malignant transformation of a teratoma are still controversial [3] . Researchers have also found that the CA125 and CA199 levels were closely related with the diameter of the teratoma and the prognosis of mature ovarian teratomas [13] . In this case, the serum CA199 level was upregulated, and the levels of the other tumor markers were within the normal range.…”
Section: Yun-xiao Zhou Et Al 24mentioning
confidence: 99%
“…Tumors show up as off-white or light yellow and brittle, and they are often accompanied by bleeding and necrosis. A malignant transformation often occurs in the inner papilla of the cyst wall, near the nodules, in the inhomogeneous enhanced portion or the thickening cyst wall [3,4,13] . Therefore, surgeons should carefully examine the cyst wall of the specimen.…”
Section: Yun-xiao Zhou Et Al 24mentioning
confidence: 99%
“…Although many studies have investigated the role of DJ-1 in PD, the molecular mechanism of DJ-1 in autophagy in PD is not completely understood. MicroRNAs (miRNAs) are a class of noncoding RNAs with a length between 18 and 25 nucleotides, which play an important role in various cellular biology processes [9]. Recently, growing evidence has revealed that multiple miRNAs are involved in the development of PD.…”
Section: Introductionmentioning
confidence: 99%